High quality draft genomic sequence of Flavihumibacter solisilvae 3-3(T) - Zhou, Gang (Stand Genomic Sci, 2015)
Flavihumibacter solisilvae 3-3(T) (= KACC 17917(T) = JCM 19891(T)) represents a type strain of the genus Flavihumibacter within the family Chitinophagaceae. This strain can use various sole carbon sources, making it applicable in industry and bioremediation. In this study, the draft genomic information of F. solisilvae 3-3(T) is described. F. solisilvae 3-3(T) owns a genome size of 5.41 Mbp, 47 % GC content and a total of 4,698 genes, including 4,215 protein coding genes, 439 pseudo genes and 44 RNA encoding genes. Analysis of its genome reveals high correlation between the genotypes and the phenotypes.